Perlindungan Hukum Pembeli Produk Tidak Sesuai Dihubungkan Undang-Undang Nomor 8 Tahun 1999 - Farhan Fatihuddin; Dede Agus; Jarkasi Anwar (Indonesian Journal Publisher, 2025)
One of the most significant digital developments is online shopping. Online shopping is highly favored by the public because it is considered to facilitate transactions. However, there are negative impacts, including dishonest merchants when marketing products, which results in losses for consumers. Therefore, the author wants to understand how legal protection is provided for consumers who lack government oversight, as well as the legal remedies that can be taken based on Law Number 8 of 1999 concerning Consumer Protection. This research method is normative-empirical law. The data used in this study are secondary and primary data. The technique for collecting secondary data is a literature study and primary data through interviews. Data processing in this study is a literature study and field. This research analysis uses a qualitative approach. The results of the study indicate that sellers are proven to not pay attention to consumer protection because they found discrepancies in the goods received, which harm consumers. It is also explained that consumers will be protected by Law Number 8 of 1999 if the consumer feels disadvantaged by the product being sold. Consumers have the right to receive comfort, security, and safety in using a product being sold to them.